New and Consolidated Therapeutic Options for Pubertal Induction in Hypogonadism: In-depth Review of the Literature - Silvia Federici; Giovanni Goggi; Richard Quinton; Luca Giovanelli; Luca Persani; Biagio Cangiano; Marco Bonomi (2021)
Abstract Delayed puberty (DP) defines a retardation of onset/progression of sexual maturation beyond the expected age from either a lack/delay of the hypothalamo-pituitary-gonadal axis activation or a gonadal failure. DP usually gives rise to concern and uncertainty in patients and their families, potentially affecting their immediate psychosocial well-being and also creating longer term psychosexual sequelae. The most frequent form of DP in younger teenagers is self-limiting and may not need any intervention. Conversely, DP from hypogonadism requires prompt and specific treatment that we summarize in this review. Hormone therapy primarily targets genital maturation, development of secondary sexual characteristics, and the achievement of target height in line with genetic potential, but other key standards of care include body composition and bone mass. Finally, pubertal induction should promote psychosexual development and mitigate both short- and long-term impairments comprising low self-esteem, social withdrawal, depression, and psychosexual difficulties. Different therapeutic options for pubertal induction have been described for both males and females, but we lack the necessary larger randomized trials to define the best approaches for both sexes. We provide an in-depth and updated literature review regarding therapeutic options for inducing puberty in males and females, particularly focusing on recent therapeutic refinements that better encompass the heterogeneity of this population, and underlining key differences in therapeutic timing and goals. We also highlight persistent shortcomings in clinical practice, wherein strategies directed at “the child with delayed puberty of uncertain etiology” risk being misapplied to older adolescents likely to have permanent hypogonadism.